The Influence of Educational Level and Professional Training on Teachers' Ability to Implement Higher-Order Thinking Skills (HOTS) Learning: The Mediating Role of Teaching Experience - Maesa Saputra; Gimin Gimin; Makdalena Makdalena (AL-ISHLAH: Jurnal Pendidikan, 2026)
The implementation of Higher-Order Thinking Skills (HOTS) is essential for equipping students with critical thinking, creativity, problem-solving, and decision-making competencies required in the twenty-first century. However, many teachers continue to face challenges in effectively integrating HOTS into classroom instruction. This study investigates the influence of teachers' educational level and professional training on their ability to implement HOTS-based learning, with teaching experience serving as an intervening variable. A quantitative survey design was employed involving teachers from public senior high schools in Pelalawan Regency, Indonesia. Data were collected using structured questionnaires and analyzed using inferential statistical techniques to examine both direct and indirect relationships among the variables. The findings indicate that teachers' educational level and participation in professional training significantly improve their ability to implement HOTS-oriented learning. Educational level and training also positively influence teaching experience. However, teaching experience does not significantly mediate the relationship between educational level, professional training, and teachers' HOTS implementation. These findings suggest that formal qualifications and continuous professional development contribute more substantially to HOTS implementation than accumulated teaching experience alone. Teachers' capacity to implement HOTS-based instruction is primarily strengthened through higher educational qualifications and sustained professional development rather than teaching experience. The study highlights the importance of designing evidence-based teacher development programs that prioritize pedagogical innovation and HOTS-oriented instructional practices. These findings provide practical implications for policymakers and school leaders seeking to enhance instructional quality and foster students' higher-order thinking competencies.